The adjunctive effect of aerobic exercise in the treatment of type 2 diabetes (有氧运动在2型糖尿病辅助治疗中的应用) - XU Yuan (许媛); LENG Mei (冷梅); JIA Nan (贾楠) (中西医结合护理)
Diabetes is one of the most important health problems today. This paper summarized the development of exercise therapy, the necessity, principles, indications and contraindications of aerobic exercise for patients with type 2 diabetes mellitus, to provide references for researchers in this field in the future. (糖尿病是社会重点关注的健康问题之一。本文通过对运动治疗的历程发展, 2型糖尿病患者有氧运动的必要性、运动原则、运动的注意事情、适应症和禁忌症等方面进行综述, 以期为糖尿病的防治提供更多参考。)